Pilot of Te Tomo mai, a child and adolescent mental health service evaluation tool for an indigenous rangatahi (youth) population. Issue 1 (2nd January 2016) - McClintock, Kahu; Tauroa, Roimata; Mellsop, Graham; Frampton, Chris
Abstract : The acceptability of Child and Adolescent Mental Health Services (CAMHS) to indigenous rangatahi (12–19-year-olds) requires investigation. Evaluation tools able to take account of the more holistic approach to the attainment of mental health that characterises Māori, the indigenous population of Aotearoa (New Zealand) with specificity to the rangatahi population are critical to this examination. The study aims were to: (1) develop an instrument and establish its psychometric properties; and (2) use the measure to establish rangatahi views on desirable CAMHS characteristics. A kaupapa Māori ( Māori -driven) research paradigm, based on the traditional Pōwhiri process of engagement and participation, particularly the components of karanga, mihimihi, whaikōrero and koha guided this quantitative research approach. These components are essential to positive contact and commitment to the study processes by researchers and participants. A self-administered survey, Te Tomo mai, was developed by modifying a North American questionnaire, the Youth Services Survey for Youth. The intent of the tool was to record rangatahi experiences and views on service acceptability. The Te Tomo mai survey incorporates questions designed to examine CAMHS delivery in the light of the Whare Tapa Whā, a Māori comprehensive model of health with a focus on culturally responsive services. This survey was completed by a cohort of 69 Māori rangatahi who were referred to six CAMHS District Health Boards in Aotearoa. The Te Tomo mai instrument factor structure, specifically the cultural factor, had similarity to the North American questionnaire from which it had been derived. This work confirms the concept that Māori desire therapeutic methods consistent with the Whare Tapa Whā, such as the importance of culture and spirituality. It further identified issues relevant to Māori rangatahi acceptability with CAMHS such as access, satisfaction and appropriateness. The participants were generally positive about the services they received from the CAMHS, which shows good acceptability of CAMHS for Māori. The Te Tomo mai instrument can prove useful if applied in Aotearoa or other similar cultural settings. It is a means of determining the cultural acceptability which will contribute to improving CAMHS delivery to rangatahi from indigenous populations.